Moisture crosslinking and properties of ethylene-vinyl acetate rubber. (27th October 2022) - Zhang, Qinghong; Wang, Gongliang; Wen, Xinlong; Hoch, Martin; Mao, Jie; Shi, Xinyan
Abstract: Ethylene-vinyl acetate rubber (EVM) is commonly crosslinked by peroxides due to its saturated main chain. Nevertheless, it is usually accompanied by side reactions to bring unexpected bubbles in products. So, it is necessary to find an alternative and environment friendly crosslinking for EVM. Herein, a silane of γ -aminopropyltriethoxysilane (APTES) containing amino groups was adopted as monomer to graft on the matrix of a modified polymer of EVM named ethylene-vinyl acetate-glycidyl methacrylate terpolymer elastomer (EVM-GMA). EVM-GMA-g-APTES was prepared through melt blending followed by the moisture crosslinking, which was achieved in a 90 °C water bath with the aid of catalyst dibutyltin dilaurate (DBTL). It was found that the characteristic absorption peak belonging to the Si–O–C bond of the purified samples appeared at 1077 cm −1 on the infrared spectrum, indicating the reaction between amino groups in APTES and epoxy groups in EVM-GMA happened successfully. Besides, the moisture curing curves of EVM-GMA-g-APTES compounds kept rising over time, which denoted that the chemical crosslink occurred and the Si–O–Si networks had been formed. Additionally, the modulus and tensile strength of moisture crosslinked samples were elevated remarkably with the increasing APTES content, and the samples with 2.5 phr APTES had relatively rational mechanical properties. Moisture crosslinking was feasible for EVM-GMA since the mechanical performance of the moisture crosslink was better than that of the peroxide crosslink system at a similar crosslink density. Graphical abstract: It was carried out successfully for the grafting reaction between ethylene-vinyl acetate-glycidyl methacrylate terpolymer elastomer (EVM-GMA) matrix and γ -aminopropyltriethoxysilane (APTES), and moisture cured EVM-GMA-g-APTES compounds were acquired through 90 °C a water bath, which showed excellent mechanical properties than that of peroxide crosslinked at a similar crosslinking density. Image 1 Highlights: The grafting reaction between APTES and EVM-GMA happened successfully. Various characterization methods (FTIR, EDS and RPA) were used to investigate the grafting mechanism of EVM-GMA-g-APTES. The moisture crosslinked EVM-GMA-g-APTES has unique mechanical properties. A new approach to develop green rubber crosslinking.